Role of yoga and meditation in sustainability and maintaining healthy life in pandemic - Chander Shekhar Sharma; Amrita Sharma (Journal of Ayurveda, 2020)
Introduction: Yoga and meditation are believed to start with the very inception of civilization and have munificent effects physically as well as mentally. As the entire world is facing dreadful COVID-19 pandemic, the concept of Yoga and meditation is the best way to keep a person in good shape, physically and mentally. Yoga along with meditation, as an integral part of our lifestyle tells us how to control the basic thought process and to stabilize oneself and integrate the state of health. Methods: Keeping the COVID-19 pandemic in mind, it is time for us to look back to utilize the treasure of Yoga and meditation for immunity, strengthening our willpower to stand the challenges of pandemic and develop resilience against negativity. Yoga usually emphasizes Asana, Pranayama, Dhyana and if practiced on daily basis will increase endorphins-feel-good-chemicals within the body and reduces cortisol levels that cause stress. Result and Conclusion: This pandemic has shown worldwide devastating effects on health-care-system, so Yoga and meditation practices could be utilized to counter the negatives of individual's physical, emotional as well as social health. In the current scenario, it is of utmost importance to deal the negative emotions with nonpharmacological interventions. The current paper focuses on the ways to protect ourselves in COVID-19 pandemic and live healthy life with regular practice of Yoga and meditation. It also highlights the role of Yoga and meditation in controlling a person's body, mind and soul. It also combines physical and mental discipline of the body and mind; to aid in managing stress, anxiety, and keep ourselves relaxed. Hence, developing a positive state of mind and promote better health to fight against the pandemic.